An investigation on the effect of cyclic displacement on the integral bridge abutment - Movahedifar, Mojtaba; Bolouri-Bazaz, Jafar (Journal of Civil Engineering and Management, 2014)
The integral bridge abutment, as a special type of retaining wall, is subject to cyclic displacement, which is due to the daily and seasonal temperature variations. The frame of this type of bridges is rigid and jointless. This requires that the slab of the bridge to be longitudinally continuous without expansion joints. This causes cyclic displacement to be imposed to the backfill material of integral bridge abutment. It should be pointed out that the omission of expansion joints helps to provide a fluent traffic and a reduction in maintenance and repair of the bridges. To investigate the impact of cyclic displacement on the loose backfill soil behaviour, an innovative laboratory retaining wall model has been designed and constructed to imitate the cyclic behaviour of backfill granular material. In addition, a numerical model, based on finite element method, has been developed to interpret the experimental results. This model was calibrated using the laboratory test data. The results indicate that the passive pressure, except for low amplitude displacement, escalates with progressive number of cycles and its distribution is not linear, which is due to the forming arch.